(untitled) (Eurasian Medical Research Periodical, 2023)
Maternal multiparity is characterized by a woman having two or more pregnancies, irrespective of the outcome (live births, stillbirths, or miscarriages). Adverse neonatal outcomes encompass various detrimental health conditions that can impact newborns.